Analisis Faktor-Faktor Penerimaan E-Wallet Menggunakan Metode Unified Theory Of Acceptance and Use of Technology 2 (UTAUT 2) (Studi Kasus Pada Mahasiswa Universitas Sriwijaya Pengguna ShopeePay) - Aurel Adelia; Dwi Rosa Indah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Technology is currently developing very quickly, one of which is the payment transaction system. The transaction service that people use to make payments is ShopeePay. Based on the results of a survey from InsightAsia entitled Consistency That Leads: E-wallet Industry Outlook 2023, the research shows the results that ShopeePay is in fourth place for e-wallet applications that are widely used in Indonesia, namely 51% of users. This proves that ShopeePay is still less attractive to the public. According to research from the Director of Customer Experience at Ipsos Indonesia, ShopeePay users are young people because their productivity level is higher than that of other groups. Based on the results of the population census in 2020, it was also noted that the majority of Indonesia's population is from generation Z, which is 27% of the total 270.2 million population of this country. This study aims to determine what factors influence the intention to use ShopeePay for Sriwijaya University students. This research was conducted using the UTAUT 2 method by adding the variables perceived trust and perceived risk. The results of this study indicate that the addition of perceived trust and perceived risk variables has a significant effect on behavioral intention. The results also show that the price, value, and habit variables also have a significant effect on behavioral intention. On the other hand, performance expectancy, effort expectancy, social influence, facilitating conditions, and hedonic motivation have no effect on behavioral intention